Social policies, risks and vulnerabilities: A gender perspective for Mauritius. Issue 3 (November 2021) - Tandrayen-Ragoobur, Verena; Gokulsing, Deepa; Irving, Zoe
Abstract: This article investigates into how gender-neutral social policies affect gender dynamics of labour market participation, family life and livelihood. Taylor-Gooby's ["New risks and social change", pp. 1–28, 2004] new social risks concept and Holmes and Jones' [Rethinking Social Protection from a Gender Lens. ODI Briefing Paper, 2010] framework are used to probe into the deepening of existing gender inequalities in the Mauritian multicultural society. The article argues that the prevailing social interventions in Mauritius overlook new social risks that have stemmed from the island's economic transformation from a monocrop to an innovation based economy. This structural change has caused women, in particular, to face new risks and vulnerabilities. To advance the argument, the article examines gender norms, lack of appropriate gender-sensitive labour market policies and gender-neutral social protection measures. A mixed methodology is used with both secondary and primary data collected via interviews with key stakeholders from public and non-governmental organisations. The findings reveal the need to connect gender-sensitive welfare policies to risks and vulnerabilities to promote greater gender inclusiveness.